The Impact of Marketing Synergy: An Analysis of the Influence of Promotion Mix Strategy, Service Quality, on Purchase Decisions at Indomaret Gading, Prambon, Nganjuk - Isyafak, Moh. Erga; Hakimah, Ema Nurzainul (Universitas Nusantara PGRI Kediri, 2025)
Research aim : The purpose of this article is to analyze the impact of synergy between promotional mix strategy and service quality on consumer purchasing decisions in Indomaret Gading, Prambon, Nganjuk. Design/Methode/Approach : In this study, a quantitative method was used with a survey method that used primary data (with a research questionnaire form containing several statements). This study took a sample of 30 respondents, and used an accidental sampling technique. The results of the questionnaire data were then analyzed by classical assumption test analysis, namely the multiple linear regression method. This questionnaire is filled with a Likert scale, which is categorized as follows: 1. Strongly Disagree (STS), 2. Disagree (TS), 3. Neutral (N), 4. Agree (S), and 5. Strongly Agree (SS). Research Finding : Based on the results of this study, through the distribution of questionnaires to Indomaret Gading, Prambon, consumers, it is proved that the promotional mix variable (X1) and the service quality variable (X2) have a significant simultaneous influence on the purchase decision at Indomaret Gading, Prambon, Nganjuk. Theoretical contribution/Originality : provide an understanding of the promotion mix and service quality in purchasing at Indomaret Gading, Prambon, Nganjuk. Practitionel/Policy implication : allocate resources proportionally to customer service to ensure the best possible shopping experience. Research limitation : Short time and respondents who are less responsive in time help fill out the research questionnaire.